2023
DOI: 10.1021/acsami.2c18837
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic, Bilayered Antimicrobial Collagen-Based Scaffold for Enhanced Healing of Complex Wound Conditions

Abstract: Chronic, nonhealing wounds in the form of diabetic foot ulcers (DFUs) are a major complication for diabetic patients. The inability of a DFU to heal appropriately leads to an open wound with a high risk of infection. Current standards of care fail to fully address either the underlying defective wound repair mechanism or the risk of microbial infection. Thus, it is clear that novel approaches are needed. One such approach is the use of multifunctional biomaterials as platforms to direct and promote wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The scaffold exhibited a functional stratum corneum, improved re-epithelialization, and the presence of elastin in the dermis, not typically present in wound healing. An improvement in mimicking the skin's architecture was obtained by creating a bilayer scaffold consisting of a collagen/chitosan film to emulate the epidermis and a collagen-glycosaminoglycan scaffold to simulate the dermis features [92]. In vitro tests revealed that the epidermal layer exhibited not only antibacterial properties but also the ability to support keratinocyte proliferation for epidermal reformation.…”
Section: Stimulating Ecm Regenerationmentioning
confidence: 99%
“…The scaffold exhibited a functional stratum corneum, improved re-epithelialization, and the presence of elastin in the dermis, not typically present in wound healing. An improvement in mimicking the skin's architecture was obtained by creating a bilayer scaffold consisting of a collagen/chitosan film to emulate the epidermis and a collagen-glycosaminoglycan scaffold to simulate the dermis features [92]. In vitro tests revealed that the epidermal layer exhibited not only antibacterial properties but also the ability to support keratinocyte proliferation for epidermal reformation.…”
Section: Stimulating Ecm Regenerationmentioning
confidence: 99%
“…These chronic wounds can become open wounds that are at high risk of infection if they do not heal properly. To address this issue, bilayer scaffolds have been developed to mimic the structure of the epidermal and dermal layers of the skin (Figure 4a) [90]. The bilayer scaffolds can be designed to promote angiogenesis and wound healing, which are the functions of endothelial cells.…”
Section: Biomimetics Skin For Wound Care Techniquesmentioning
confidence: 99%
“…The traditional approach to wound dressings has limitations in supporting complex wound healing processes, as they primarily focus on sealing the wound, absorbing exudate, and maintaining a moist environment. However, by incorporating ECM components like collagen, glycosaminoglycan, or hyaluronic acid into traditional dressings, it can actively promote epithelialization, angiogenesis, and collagen deposition, thereby enhancing the overall wound healing process [90,237,238]. (2) Biomimetics presents a promising approach to wound care technology and has the potential to extend its benefits to the treatment of other diseases and conditions.…”
Section: Propose Future Directions For Research and Developmentmentioning
confidence: 99%
“…The dressing exhibits a structure similar to that of natural skin, successfully inhibiting bacterial growth and promoting angiogenesis. This dressing is an excellent candidate for enhancing diabetic wound healing ( 111 ).…”
Section: Classification and Active Ingredients Of Dressingsmentioning
confidence: 99%